An economic impact assessment of toll roads, with specific reference to the impact on alternative roads between the Pumulani and Hammanskraal toll gates - Breitenbach, Marthinus Christoffel (University of Pretoria, 2013)
Dissertation (Magister Commercii)--University of Pretoria, 2007.